Virtual Laboratory as A New Educational Trend Post Covid-19: An Effectiveness Study - Doni Tri Putra Yanto; Maryatun Kabatiah; Hermi Zaswita; Nizwardi Jalinus; Refdinal Refdinal (Universitas Pendidikan Ganesha, 2022)
The virtual laboratory is one of the popular trends for implementing remote learning in vocational education during the COVID-19 to Post-COVID-19 pandemic, either as a substitute or as a complement to learning in a Real Laboratory. This study discusses the effectiveness analysis of the virtual laboratory as a practicum learning media to support remote or online learning implementation. The purpose of this study was to analyses the virtual laboratory's effectiveness as a learning media in the learning process of the Power Electronics Practicum in Post-COVID-19. The type of research applied is a Pre-experimental Design with a One-Group Pretest-Posttest design. The Performance Appraisal Rubric is used as an instrument to collect research data. The virtual laboratory's effectiveness is known from the difference analysis of pretest and post-test scores using the Paired Sample T-test. Meanwhile, Cohen's d effect size analysis was used to determine the effect size. The results showed that the virtual laboratory was effectively used as a practicum learning media with a large effect category. Thus, it can be concluded that the virtual laboratory can be an effective choice for implementing practical learning in supporting the implementation of remote learning.